2012
DOI: 10.5402/2012/650892
|View full text |Cite
|
Sign up to set email alerts
|

The Floppy Eyelid Syndrome: Evaluating Lid Laxity and Its Correlation to Sleep Apnea Syndrome and Body Mass Index

Abstract: Background. The aim of this study is to present a method of lid laxity evaluation and investigate whether there is an association between floppy eyelid syndrome (FES) and body mass index (BMI) in sleep apnea syndrome (SAS) patients compared to normal subjects. Method. A total of 135 participants (81 patients with SAS and 54 normal subjects) had a full ophthalmologic examination. The presence of FES was estimated in relation to SAS and BMI. Results. The floppy eyelid was characterized “hyperelastic,” “FES stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
0
25
1
Order By: Relevance
“…Beis has proposed that FES is an extreme situation of lid laxity. Our results could potentially broaden the already known relationship regarding sleep position and FES [15]. The difference we have found in the correlation between the preferred sleep side and the morbidity between the two groups may stems from the fact that hypoxia is more dominant in the pathophysiology of ectropion than entropion.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Beis has proposed that FES is an extreme situation of lid laxity. Our results could potentially broaden the already known relationship regarding sleep position and FES [15]. The difference we have found in the correlation between the preferred sleep side and the morbidity between the two groups may stems from the fact that hypoxia is more dominant in the pathophysiology of ectropion than entropion.…”
Section: Discussionmentioning
confidence: 56%
“…The primary pathology of both involutional ectropion and FES is lid laxity [15]. Figueira et al also found that healthy patients without eyelid pathology demonstrate a correlation between the side on which they historically or customarily sleep and the laxity of the ipsilateral upper eyelid [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD asymmetry ie >or = 0.2 difference between two eyes 4. IOP asymmetry ie > or = 3mmHg difference with IOP > or = 16 These suspects were further evaluated by complete glaucoma workup Blood sugar levels:-random, fasting and post prandial levels were done.…”
Section: Materials and Methods:-mentioning
confidence: 99%
“…The patient was diagnosed with severe obstructive sleep apnea syndrome (OSAS) and his symptoms improved with automatic continuous positive airway pressure (CPAP) treatment at 9 cmH2O pressure. Floppy eyelid syndrome is a clinical entity which has already been extensively investigated in terms of clinical characteristics, local and systemic associations, and treatment since its first description (1). Recent studies have suggested a relationship between OSAS and FES (2).…”
Section: Gevşek Gözkapağı Sendromu Ile Obstrüktif Uyku Apnesi İlişkisimentioning
confidence: 99%